Effects of an extra-high slaughter weight and a low-lysine diet on growth and meat quality of finishing gilts - Lee, Chul Young; Lee, Eun-Yeong; Park, Tae-Whan; Jeong, Yeon-Hae; Son, Yu-Min; Oh, Sang-Hyon; Joo, Seon-Tea; Jang, Jae-Cheol (Journal of animal science and technology, 2024)
The present study aimed to find out the feasibility of increasing the meat quality of finishing gilts by increasing their slaughter weight (SW) to an extra-high (XH) level and also by using a low-lysine (lys) diet in XH-weight pig production. Twenty-four gilts and eights barrows were divided into four treatments (T) by gender, SW, and diet: T1 (barrow; 116-kg SW; Medium [Med]-lys [0.80%] diet), T2 (gilt; 116-kg SW; Med-lys), T3 (gilt; XH [150 kg] SW; Med-lys), and T4 (gilt; XH SW, Low-lys [0.60%]). Growth performance from 85 kg of body weight to SW was measured only for T3 and T4. All animals were slaughtered at their target SW, followed by physicochemical analyses and sensory evaluation on the muscle (LL). Average daily gain did not differ between T3 and T4. Dressing percentage was greater for T3 vs. T2. Backfat thickness was greater for T1 vs. T2 and T3 vs. T2, not being different between T3 and T4. The LL pH was lower and Warner-Bratzler Shear force value was greater for T3 vs. T2. Other physicochemical measurements including the intramuscular fat content were not different or different narrowly if different at all ( < 0.05) between T3 and T2 or T4, but not between T1 and T2. The percentages of major fatty acids including 16:0, 18:0, 18:1, and 18:2 in LL, which did not differ between T2 and T3, differed between T3 and T4 apparently resulting from a difference in composition of the ingredients of the two diets. The sensory texture score was greater for T3 vs. T2 in fresh LL; in cooked LL, juiciness and umami scores were greater for T3 vs. T2, flavor score being less for T4 vs. T3. The gender effects on physicochemical and sensory pork quality were small, if any. Overall, the meat quality of finishing gilts could be improved by increasing the SW to the XH level, but not by using the Low-lys diet, suggesting that it will be feasible to produce XH-weight market gilts if the increased meat quality can make up for the expected decrease in production efficiency accompanying the increased SW.